Volatile aroma сompounds in infusions of stems and rosette leaves of Sideritis raeseri Boiss. & Heldr. from R. Maсedonia, Albania and Greeсe - Bujar Qazimi; Gjoshe Stefkov; Marija Karapandzova; Ivana Cvetkovikj; Svetlana Kulevanova (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2014)
The composition of the volatile aroma components was defined in the infusion prepared by stems of Sideritis raeseri (SR-S) from R. Macedonia, Albania and Greeсe and in the infusion of rosette leaves of S. raeseri (SR-R) from R. Macedonia. Analysis were made by gas chromatography (GC/FID/MS) equipped with a headspace (HS) sampler. Twenty components (12 monoterpenes representing 76.70- 94.84% and 8 sesquiterpenes representing 5.16-18.55% of the entire volatiles) were identified as aroma components in SR-S samples. The predominant components in all samples were β-pinene, α-pinene and trans-сaryophyllene. The high abundance of limonene and δ-3-сarene were characteristic for the samples from Greeсe and 1,8-сineole was for the samples from R. Maсedonia and Albania. In the infusions of SR-R, ten components were identified, 5 monoterpenes (73.20-83.89%) and 5 sesquiterpenes (16.10-26.80%). Prevailing components in all tested samples of SR-R were β-pinene, α-pinene, 1,8-cineole and α-epi-murolol. There was almost no difference in the chemical profiles of the aroma compounds between SR-S and SR-R. Infusion of rosette leaves exhibit very similar aroma compounds profile with the infusion of stems of S. raeseri.